PENGARUH SOCIAL MEDIA MARKETING, EVENT MARKETING, DAN CELEBRITY ENDORSEMENT DALAM MENINGKATKAN CUSTOMER LOYALTY (STUDI KASUS PADA NONGKASKI COFFEE & EATERY WATES) - Wirawan, Ridwan; Muslih, Basthoumi; Suprajitno, Edy Djoko (Universitas Nusantara PGRI Kediri, 2023)
This study aims to determine the relationship between social media marketing, event marketing, and celebrity endorsement partially and simultaneously towards customer loyalty of Nongkaski Coffee & Eatery Wates. This type of research is quantitative causality. The population in this study were all visitors to Nongkasi Coffee & restaurant. Determination of the sample using a simple random sampling technique with a total sample of 150 people by multiplying 15 indicators by 10 times. Data collection using a questionnaire. The analytical tool used is multiple linear regression analysis. The results of the study are that social media marketing partially has no effect on customer loyalty, while event marketing and celebrity endorsements partially and significantly affect customer loyalty. Simultaneously social media marketing, event marketing, and celebrity endorsements have a significant and significant effect on customer loyalty by 29.5%.